2016
DOI: 10.16965/ijar.2016.346
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sub Carinal Angle of Human Trachea by Computerized Tomography

Abstract: The study of bronchial tree is done by both invasive and non-invasive techniques like cadaveric dissection, bronchograms, virtual bronchoscopy, Computed Tomography (CT) scan and Magnetic Resonance Imaging (MRI) scan. Materials and Methods: The subcarinal angle of trachea was measured on chest CT scans of 110 normal adult individuals in the age group of 10-70 years (69 males and 41 females) attending the department of Radiodiagnosis at Government Medical College, Aurangabad. Result: The mean value for subcarina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
(7 reference statements)
1
11
0
Order By: Relevance
“…Chunder and Guha [14] study found that the mean SCAs in the 0-15 years, 16-25 years, 26-40 years, 41-55 years, and >55 years age groups were 61.4°, 52.9°,49.2°, 48.2°, and 54° in females and 64.3°, 56.4°, 58.4°, 57.1°, and 59.5° in males. It concluded that in the adult group there was a decrease in the SCA with an increase in the age which was similar to the study conducted by Khade et al [10], who also demonstrated a decrease in the SCA with an increase in the age group which is similar to our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Chunder and Guha [14] study found that the mean SCAs in the 0-15 years, 16-25 years, 26-40 years, 41-55 years, and >55 years age groups were 61.4°, 52.9°,49.2°, 48.2°, and 54° in females and 64.3°, 56.4°, 58.4°, 57.1°, and 59.5° in males. It concluded that in the adult group there was a decrease in the SCA with an increase in the age which was similar to the study conducted by Khade et al [10], who also demonstrated a decrease in the SCA with an increase in the age group which is similar to our study.…”
Section: Discussionsupporting
confidence: 93%
“…Extension of the head and elongation of bronchial tree by inspiration will cause the carinal angle to become narrow. On the other hand, shortening of the bronchial tree widens the carinal angle [10]. In our study, all the CT scans of the thorax were only taken in inspiration phase without extension of the head.…”
Section: Discussionmentioning
confidence: 98%
“…The trachea is a cylindrical cartilaginous tube meant for passage of air between larynx and lungs and extends superiorly from cricoid cartilage and ends inferiorly at carina. 1,2 It is about 10-11cm in length and extends from the level of sixth cervical vertebra to the upper border of fifth thoracic vertebra. 1 It divides into right and left principal bronchi which enter the corresponding lungs and progressively branch off throughout the entire lung to form trachea-bronchial tree.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is about 10-11cm in length and extends from the level of sixth cervical vertebra to the upper border of fifth thoracic vertebra. 1 It divides into right and left principal bronchi which enter the corresponding lungs and progressively branch off throughout the entire lung to form trachea-bronchial tree. Subcarinal angle (SCA) is an angle of divergence between the right and left main stem bronchi.…”
Section: Introductionmentioning
confidence: 99%
“…All previous studies measured SCA on the postero-anterior chest radiograph and coronal reformatted chest CT in respect to age, gender, thoracic index patient habitus and body mass index. [1][2][3][4][5][6][7][8][9][10] Previous studies have shown that SCA varies in relation to various independent factors like age, sex and patient habitus. The reference value mentioned by previous studies may not be extrapolated in our population.…”
Section: Introductionmentioning
confidence: 99%